Association of Elevated NT-proBNP With Myocardial Fibrosis in the Multi-Ethnic Study of Atherosclerosis (MESA) - Liu, Chia-Ying; Heckbert, Susan R; Lai, Shenghan; Ambale-Venkatesh, Bharath; Ostovaneh, Mohammad R; McClelland, Robyn L; Lima, João A C; Bluemke, David A (Journal of the American College of Cardiology, 2017)
Serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) is considered a marker that is expressed in response to myocardial strain and possibly fibrosis. However, the relationship to myocardial fibrosis in a community-based population is unknown. The authors evaluated the relationship between cardiac magnetic resonance (CMR) measures of fibrosis and NT-proBNP levels in the MESA (Multi-Ethnic Study of Atherosclerosis) study. A total of 1,334 participants (52% white, 23% black, 11% Chinese, 14% Hispanic, and 52% men with a mean age of 67.6 years) at 6 sites had both serum NT-proBNP measurements and CMR with T1 mapping of indices of fibrosis at 1.5 T. Univariate and multivariable regression analyses adjusting for demographics, cardiovascular risk factors, and left ventricular (LV) mass were performed to examine the association of log NT-proBNP with CMR T1 mapping indices. In the fully adjusted model, each 1-SD increment (0.44 pg/ml) of log NT-proBNP was associated with a 0.62% increment in extracellular volume fraction (p < 0.001), 0.011 increment in partition coefficient (p < 0.001), and 4.7-ms increment in native T1 (p = 0.001). Results remained unchanged after excluding individuals with clinical cardiovascular disease or late gadolinium enhancement (n = 167), and after replacing LV mass by LV end-diastolic volume in the regression models. Elevated NT-proBNP is related to subclinical fibrosis in a community-based setting. (Multi-Ethnic Study of Atherosclerosis [MESA]; NCT00005487).